Determinants of Profitability: A Comparative Study of Textile and Cement Sector of Pakistan - Mansoor, Hadia (Information Management and Business Review, 2020)
The purpose of this study is to find the internal and external determinants of profitability of textile and cement sector of Pakistan. Secondary data is collected from “Financial Statement Analysis of companies (non-financial) listed at Karachi Stock Exchange” for the period of 2005-2010 by using the random and convenient sampling technique. Dependent variables consist of ROA and ROE and independent variables are liquidity, leverage, growth, capital intensity, size and market share. Out of the six variables, first four represents the internal factors and remaining two are external factors. Panel data analysis is applied to find the relationship among dependent and independent variables. The results of this study indicate that the liquidity and leverage impact significantly in the textile sector but growth, capital intensity, size and market share have no relevance with the profitability of this sector. In case of cement sector, liquidity, leverage and growth shows considerable effect while other factors are insignificant. This study is useful for the management of these sectors while carrying out any decision regarding internal and external variables.